Outbreak investigation of acute febrile illness from the Himalayan foothills: Solving the puzzle of fever - Satapathy, Prakasini; Goel, Kapil; Sharma, Vikrant; Sarkar, Subhabrata; Kang, Mannat; Dhingra, Shefali; Bora, Ishani; Kaur, Kanwalpreet; Arora, Neeraj; Aggarwal, Arun; Ratho, Radha Kanta (Frontiers in Pharmacology, 2023)
In September 2022, Panchkula Civil Hospital reported an outbreak of ‘mystery fever’ in Pinjore, located in the Himalayan foothills, Haryana, North India. There was an upsurge of fever cases i.e., 842 reported fever cases with casualties in 15 cases. Blood samples were taken from suspected patients (n = 58) with AFI and subjected to serology of dengue, chikungunya, Japanese encephalitis (JE), leptospira and scrub typhus. The samples were also screened for West Nile & Zika virus RNA using by real-time PCR. Viral strains were characterized by sequencing. Of the 58 cases of AFI, Dengue could be identified in 45 (77.58%) followed by JE and Chikungunya in 2 cases each (3.44%) respectively. Among Dengue positive cases 44 had mono-infection (97.77%) and 1 patient had dengue and JE. None were positive for Zika, West Nile, Scrub typhus, and Leptospira with the testing protocol. Four patients developed dengue with warning signs, such as abdominal pain in one patient and recurrent vomiting in the remaining three. The dengue serotype could be determined in 17 samples and revealed serotype 2. Molecular evolution analysis based on complete envelope gene revealed that all DENV-2 strains (n=13) that circulate in the outbreak area belong to the DENV-2 cosmopoliton genotype. In the early stages of infection, relying only on clinical manifestations is ineffective, so both molecular and serological assays along with clinical diagnosis are noteworthy for determining the aetiology of AFI.